2016
DOI: 10.1007/s10610-016-9310-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparing crime reporting factors in EU countries

Abstract: Through crime-reporting citizens make their security needs explicit to the police. This information helps the police in the allocation of resources. In the European Union, there are significant differences among countries, both in terms of overall and specific crime-reporting rates. Factors highlighted by the literature that might explain these differences are not entirely satisfactory. There is little comparative research, and most published studies are nation-centred, based on the experience of central and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 36 publications
(60 reference statements)
1
38
1
5
Order By: Relevance
“…Moreover, victims who are married (Baumer and Lauritsen, 2010;Gutierrez and Kirk, 2015;Schnebly, 2008) or who have a partner (Goudriaan et al, 2004) have been shown to be more likely to report crime than victims without a partner. Results with respect to the victim's educational level are mixed, with studies showing a negative association with reporting violent crime (Goudriaan, 2006;Zaykowski, 2010), a positive association with reporting property crime (Gutierrez and Kirk, 2015), and no significant association with reporting various types of crime (e.g., Baumer and Lauritsen, 2010;Guzy and Hirtenlehner, 2015;Khondaker et al, 2015;Schnebly, 2008;Torrente et al, 2016). The same is true for the association between the income of victims and their crime reporting behavior, as studies have shown positive (e.g., Goudriaan et al, 2004;Robert et al, 2010;Torrente et al, 2016), negative (Schnebly, 2008), and insignificant relationships (e.g., Guzy and Hirtenlehner, 2015;Zaykowski, 2012).…”
Section: Socio-demographicsmentioning
confidence: 99%
“…Moreover, victims who are married (Baumer and Lauritsen, 2010;Gutierrez and Kirk, 2015;Schnebly, 2008) or who have a partner (Goudriaan et al, 2004) have been shown to be more likely to report crime than victims without a partner. Results with respect to the victim's educational level are mixed, with studies showing a negative association with reporting violent crime (Goudriaan, 2006;Zaykowski, 2010), a positive association with reporting property crime (Gutierrez and Kirk, 2015), and no significant association with reporting various types of crime (e.g., Baumer and Lauritsen, 2010;Guzy and Hirtenlehner, 2015;Khondaker et al, 2015;Schnebly, 2008;Torrente et al, 2016). The same is true for the association between the income of victims and their crime reporting behavior, as studies have shown positive (e.g., Goudriaan et al, 2004;Robert et al, 2010;Torrente et al, 2016), negative (Schnebly, 2008), and insignificant relationships (e.g., Guzy and Hirtenlehner, 2015;Zaykowski, 2012).…”
Section: Socio-demographicsmentioning
confidence: 99%
“…La policía, como servicio público, debe ofrecer igual acceso a la seguridad a todos los ciudadanos y entidades; sin embargo, la creciente polarización socioeconómica lo dificulta. En ocasiones, los recursos públicos favorecen más a unos sectores que a otros (Torrente et al, 2016). Estas alianzas privilegiadas, con frecuencia, se justifican en aras de una mayor eficacia policial o corresponsabilidad en la seguridad.…”
Section: Grupos De Interés Y Poderes Socioeconómicosunclassified
“…In lijn met dit perspectief blijkt uit diverse studies dat er vaker aangifte gedaan wordt bij vermogensdelicten dan bij gewelds-en vandalismedelicten (o.a. Bowles, Reyes & Garoupa, 2009;Goudriaan, 2006;Torrente, Gallo & Oltra, 2016). Omdat er bij diefstal een grotere kans is op een schadevergoeding dan bij geweldsdelicten en vandalisme, zijn de baten van aangifte doen vergroot.…”
Section: Economisch Perspectiefunclassified
“…Voor andere buurtkenmerken zoals de urbanisatiegraad, sociale cohesie, etnische samenstelling, prevalentie van criminaliteit en residentiële mobiliteit geldt dat uit de literatuur gemengde resultaten naar voren komen (o.a. Goudriaan, Wittebrood & Nieuwbeerta, 2006;Hart & Colavito, 2011;Schnebly, 2008;Slocum et al, 2010;Torrente, Gallo & Oltra, 2016).…”
Section: Sociologisch Perspectiefunclassified
See 1 more Smart Citation